Body size, trophic position, and the coupling of different energy pathways across a saltmarsh landscape. Issue 6 (9th September 2021) - Keppeler, Friedrich W.; Olin, Jill A.; López‐Duarte, Paola C.; Polito, Michael J.; Hooper‐Bùi, Linda M.; Taylor, Sabrina S.; Rabalais, Nancy N.; Fodrie, F. Joel; Roberts, Brian J.; Turner, R. Eugene; Martin, Charles W.; Jensen, Olaf P.
Abstract: Body size is considered an important structuring mechanism of food webs because consumers are usually larger and more mobile than their prey and may couple energy among habitats. We explored the links among trophic position (TP), body size, and the coupling of different energy channels (phytoplankton and C4‐marsh plants) in a saltmarsh landscape in the northern Gulf of Mexico—a dynamic system considered weakly shaped by biotic interactions. Body size was positively associated with TP, and this relationship was stronger in the phytoplankton pathway vs. the C4‐marsh pathway. There was a gradual increase in the coupling of phytoplankton and C4‐marsh plants at larger body sizes and higher TP. Phytoplankton supported longer food chains and larger body sizes than C4‐marsh plants. Results support predictions of the landscape theory for food web architecture and indicate that the role of body size in determining trophic interactions may vary across food web compartments.